Perbandingan Dinamika Kelembagaan Ekonomi Islam di Arab Saudi dan Singapura: Tantangan, Strategi Penguatan, dan Implikasinya bagi Pengembangan Ekonomi Islam di Indonesia. - Lailatun Lathifah; Naufal Luthfi Alifa (STAI Nurul Islam Mojokerto, 2026)
This study aims to compare the dynamics of Islamic economic institutions in Saudi Arabia and Singapore to understand the challenges, strengthening strategies, and their implications for Islamic economic development in Indonesia. The scope of the study covers geographic conditions, economic characteristics, institutional models, and regulatory and innovation strategies for Islamic finance in both countries. The results show that Saudi Arabia developed Islamic economic institutions based on sharia legitimacy and national integration, while Singapore adopted a flexible model oriented towards global markets and innovation. These differences in approach result in their respective strengths and limitations. The study concludes that Indonesia can adopt a combination of the Saudi and Singaporean models through strengthening regulations, harmonizing sharia standards, digital innovation, and improving human resource quality to build competitive and sustainable Islamic economic institutions.